Evidence of insufficient quality of reporting in patent landscapes in the life sciences - Smith, J; Arshad, Z; Carr, A; Brindley, D (Springer Nature, 2017)
Despite the importance of patent landscape analyses in the commercialization process for life science and healthcare technologies, the quality of reporting for patent landscapes published in academic journals is inadequate.